Edukasi, Pelatihan Dan Pemberdayaan Kader Kesahatan Posyandu Cakranegara Utara Tentang Skrining Rapid Dbd Ns-1 - Resnhaleksmana, Ersandhi; Srigede, Lalu; Getas, I Wayan (Universitas Mataram, 2023)
Handling infectious diseases, such as Dengue Hemorrhagic Fever (DHF), will be successful if it involves all levels of society. One of the spearheads of health service activities is posyandu cadres. Posyandu cadres' knowledge regarding infectious diseases, especially Dengue Hemorrhagic Fever (DHF), is still lacking, and it is known that the viral infectious disease that remains a scourge on health is dengue hemorrhagic fever. Dengue Hemorrhagic Fever (DHF) often causes health problems for the community and often causes outbreaks of Extraordinary Events (KLB) with large numbers of deaths. Techniques that can be used are education about Dengue and training of mosquito larvae monitors for cadres at Community Health Centers. The aim of carrying out this activity is to increase cadres' knowledge of Dengue Hemorrhagic Fever and the Rapid Test for Dengue Dengue NS-1. The target of this activity is the North Cakranegara posyandu cadre group. The results of the outreach and training showed an increase in cadres' knowledge and skills regarding the prevention and use of the NS-1 Dengue Rapid Test.